2003
DOI: 10.1002/pssb.200301604
|View full text |Cite
|
Sign up to set email alerts
|

LiH under high pressure and high temperature: A first‐principles study

Abstract: The behaviours of LiH under high pressure and high temperature are studied using first-principles calculation. We have studied the pressure dependence of the electronic energy band gap as well as possible insulator-metal phase transition. We have calculated temperature, heat capacity, and equation-of-state along the principal Hugoniot. The calculated results agree well with the experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…The corresponding pressure is $ 327 GPa. This is in accord with the predictions of Wang et al 2 and Zurek et al 19 and not with Gou et al 17 and Zhang et al 18 The calculated 300 K isotherm is plotted in Fig. 2 along with the experimental data.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The corresponding pressure is $ 327 GPa. This is in accord with the predictions of Wang et al 2 and Zurek et al 19 and not with Gou et al 17 and Zhang et al 18 The calculated 300 K isotherm is plotted in Fig. 2 along with the experimental data.…”
Section: Resultssupporting
confidence: 88%
“…As far as structural stability of this compound under high pressure is concerned, widely differing results have been reported in literature. 1,2,[16][17][18][19] On the basis of psuedopotential calculations within local density approximation (LDA), Martins 16 predicted NaCl type (B1 phase) to CsCl type (B2 phase) structural phase transition at $ 450 GPa, whereas, theoretical calculations by Gou et al 17 using ionic overlap compression model found this transition to occur at $ 85 GPa. In contrast to this, the x-ray diffraction measurements in DAC carried out by Loubeyre et al 10 do not show any phase transition up to 94 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…At high pressures, the slight deviation between 2DM results and the experimental data might be due to the anharmonicity that was not included in our first-principles QHA calculations, as implied by the QTB-MD 24 calculations.Moreover, we also investigate the isotopic effects on the B1-B2 solid phase boundaries of lithium hydrides. Previous theoretical studies mainly focused on this transition of 7 LiH at 0 and 300 K, and estimated a transition pressure spanning from 200 to 500 GPa[9][10][11][12][13][14][15][16] .The finite temperature phase transition and isotopic effects, however, are not explored. The calculated B1-B2 solid phase boundaries of 6 LiH,6 LiD,6 LiT, and 7 LiT are displayed inFig.…”
mentioning
confidence: 99%
“…9. Experimental results compared to previous measurements from the Z machine [51], from gas guns [38] and from underground tests [39,53]; theoretical predictions from QMD (this work, in close agreement with [51,52,58] and density functional theory [59]; and tabulated equation of state models [58,61]. Precompressed data points are shown as diamondshaped red symbols FIG.…”
Section: Resultsmentioning
confidence: 61%